Anaerobic treatment of olive mill wastewater and piggery effluents fermented with Candida tropicalis - Gregorio, Martinez-Garcia; Anbu Clemensis, Johnson; Robert T., Bachmann; Ceri J., Williams; Andrea, Burgoyne; Robert G.J., Edyvean (Elsevier B.V., 2009)
Link to publisher's homepage at http://www.elsevier.com/wps/find/homepage.cws_home